The governance structure on the role of internal auditors in environmental auditing practices: cases of Malaysian local organisations - Mohd Jamil, Muthyaah; Zainal Abidin, Nor Hafizah; Mohd Alwi, Norhayati (Elsevier Limited, 2022)
This study investigates how governance structures’ internal auditors play their roles in environmental auditing practices. This study used interpretative research focusing on multiple case studies: two Malaysian Local Govern- ments with single-case design and environmental auditing. This study utilised three methods of data collection: document analysis, observations and interviews. This study used thematic analysis using Atlas.Ti software. This study concludes that governance structures such as NGO Watchdog Group, independence of the internal audit department, tenure of Chairman, multiple functions and review meetings inﬂuence the roles of the internal audit department. This study explores the environmental auditing practices using expectation development by Role Theory to illustrate the process of environmental auditing practices. The ﬁndings outline how to construct environmental auditing practices and improve the eﬀectiveness of the practices in government organisations.